Kajian Kinerja Pelayanan Puskesmas Pringsurat Temanggung - Budisusanti, RR. Hesti Puspitasari (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
Pringsurat public health center as the place of public service that prepare to serve the people of Pringsurat district and the people surrounding there. To reach the optimal public health it’s necessary the health service for the qualified people. Beside scoring from the health official, performance scoring also include external scoring, the opinion of the society as the user of public health center. The aim of this observation is to study service performance of the public health center Pringsurat Temanggung. The results of this study are the characteristic service users, the more age at more productive, female more dominant ast to serve to the public health center, the education at the middle grad e, kind of work more on housewife, the middle income below and the distance of living to the public health center average 5 – 10 km. The conclusion of this study is the service performance externally or quality was good and satisfying service users, while internally or quantity is still not good.